2019
DOI: 10.21608/edj.2019.72574
|View full text |Cite
|
Sign up to set email alerts
|

An-invitro comparison of Thermocycling Effect on Micro- hardness and Micro-tensil bond strength of Nano composite denture teeth

Abstract: Purpose: The purpose of this study was an evaluation of the effect of thermocycling on microhardness and microtensile bond strength (μTBS) of the cross-linked acrylic and nanocomposite teeth to the acrylic denture base. Materials and methods: twelve teeth of the upper denture teeth were selected. Six teeth of nano-hybrid composite resin denture teeth and six cross-linkedacrylic teeth. These teeth, together with theacrylic resin bases, have been fixed to a micro-sawing machine to form 120 microbeam samples. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies have shown that bond strength between acrylic teeth and denture base resins could be affected by aging processes such as thermocycling procedure, which could decrease the overall bond strength. 40 , 41 Baia et al 42 concluded that prolonged bleaching either post- and pre-restoration using 4% hydrogen peroxide decreased tooth bonding. However, in another study, decreased bond strength was found in teeth bonded to CAD/CAM and 3D printed denture base resins, when compared to the heat cured acrylic resin, with no significant influence following aging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that bond strength between acrylic teeth and denture base resins could be affected by aging processes such as thermocycling procedure, which could decrease the overall bond strength. 40 , 41 Baia et al 42 concluded that prolonged bleaching either post- and pre-restoration using 4% hydrogen peroxide decreased tooth bonding. However, in another study, decreased bond strength was found in teeth bonded to CAD/CAM and 3D printed denture base resins, when compared to the heat cured acrylic resin, with no significant influence following aging.…”
Section: Discussionmentioning
confidence: 99%